Impact of reforestation project on livelihood and awareness on forest conservation among the local community : a case study in Kampung Tong Nibong, Serian - Kotaro, Ozawa (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study is conducted to determine impact of reforestation project on local communities. Specifically, the objectives of this study are to identify impact of the reforestation project implemented by Japan Malaysia Association in cooperation with Forestry Department Sarawak in Apeng Forest Reserve on livelihood of and forest conservation awareness among participating community of Kampung Tong Nibong, Serian. Socioeconomic impacts of the project on the participating households are also identified. In order to obtain data necessary to achieve research objectives, face-to-face interview, which helps to obtain respondents’ demographic and socioeconomic information as well as their perception of forest conservation, with 14 participants of the reforestation project was carried out in November 2014. The findings of this study show that the reforestation project conducted in Apeng Forest Reserve has positive effects on socioeconomic status of participating households in Kampung Tong Nibong. These include increase in job opportunity and household’s income as well as better understanding and recognition of the important role of forest in sustaining livelihoods of the community. The findings of this study also reveals that land issues caused by the expansion of oil palm plantation and restriction on agricultural activities within the forest reserve area have resulted the non-participating villagers’ encroachment into Apeng Forest Reserve. Therefore, it is suggested that the project should expand its scale to involve more villagers in reforestation activities so that the forests would remain undisturbed from deforestation while the community of Kampung Tong Nibong as a whole would be able to enhance their socioeconomic status and awareness on forest conservation.